PENGARUH PELATIHAN DAN MOTIVASI KARYAWAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. PELABUHAN INDONESIA III (PERSERO) CABANG TANJUNG EMAS SEMARANG - Zida IIayya Mua'rrifa; Rustono - Rustono; Sri - Wahyuni (Politeknik Negeri Semarang, 2015)
The purpose of this reseach was to identifythe influence of training and workingmotivation to employees satisfaction of PT.Pelabuhan Indonesia III (Pesero) CabangTajung Emas Semarang. Questionnaire,Interview and literature studies are theinstruments used to collect data.Questionnaires were distributed to 60employee as respondents. The dataanalysis used the method of multiple linierregression coefficient analysis. Regressionanalysis was used to determine theinfluence of training and workingmotivation to emlpoyee performance.Data were processed using SPSS v.16.0.The result of this study is that thecalculation of regression coefficientobtained Y= 1,882e + 0,560 X1 + 0,349X2.The training and motivation ofemployees have a significant effect onemployee job satisfaction. for trainingvariables showed a positive and significantinfluence. As for the variable employeesmotivation also showed the same resultsare positive and have significant effect onemployee Job satisfaction